People before products : - Matsushita, Konosuke (PHP Institute INC., 1992)
Management based on the principle of collective wisdom not only leads to better business performance, it also fosters the growth of individual human potential. From my own experience and observations, employees grow in insight and ability even if their supervisor is the most average of people, as long as that supervisor is a willing listener and is determined to work harder than anyone else to mobilize the human resources available to him or her. This is how humankind’s tremendous potential will be fully realized.